Combination immune checkpoint blockade with ipilimumab and nivolumab in the management of advanced melanoma. (3rd March 2016) - Spain, Lavinia; Larkin, James
ABSTRACT: Introduction : The use of immune checkpoint inhibitors for the treatment of advanced melanoma has evolved beyond monotherapies such as ipilimumab and nivolumab to combination strategies involving both. This combination approach results in response rates around 60% and superior progression-free survival compared with ipilimumab monotherapy (median 11.5 versus 2.9 months). Areas covered : A comprehensive literature search was undertaken including search terms of 'ipilimumab and nivolumab' and 'combination immune checkpoint therapy'. Relevant information contained in abstracts and conference presentations was included. This article summarizes the mechanism of action, efficacy and safety of combination ipilimumab and nivolumab across Phase I, II and III clinical trials. It also describes the place of combination therapy in the current market of advanced melanoma treatment options. Expert Opinion : Efficacy for the combination approach is seen across a wide array of subgroups and occurs regardless of BRAF mutation status. Counterbalancing the apparent advantages, combination ipilimumab with nivolumab is associated with a high rate (55%) of grade 3/4 adverse events leading to discontinuation in a third of those treated. Most of these are manageable and do not appear to compromise durability of response. Overall survival information is currently immature but appears promising.